Transonic Turbulence and Density Fluctuations in the Near-Sun Solar Wind - L.-L. Zhao; A. Silwal; X. Zhu; H. Li; G. P. Zank (The Astrophysical Journal Letters)
We use in situ measurements from the first 19 encounters of Parker Solar Probe and the most recent five encounters of Solar Orbiter to study the evolution of the turbulent sonic Mach number M _t (the ratio of the amplitude of velocity fluctuations to the sound speed) with radial distance and its relationship to density fluctuations. We focus on the near-Sun region with radial distances ranging from about 11 to 80 R _⊙ . Our results show that (1) the turbulent sonic Mach number M _t gradually moves toward larger values as it approaches the Sun, until at least 11 R _⊙ , where M _t is much larger than the previously observed value of 0.1 at and above 0.3 au; (2) transonic turbulence with M _t  ∼ 1 is observed in situ for the first time and is found mostly near the Alfvén critical surface; (3) Alfvén Mach number of the bulk flow M _A shows a strong correlation with the plasma beta, indicating that most of the observed sub-Alfvénic intervals correspond to a low-beta plasma; (4) the scaling relation between density fluctuations and M _t gradually changes from a linear scaling at larger radial distances to a quadratic scaling at smaller radial distances; and (5) transonic turbulence is more compressible than subsonic turbulence, with enhanced density fluctuations and slightly flatter spectra than subsonic turbulence. A systematic understanding of compressible turbulence near the Sun is necessary for future solar wind modeling efforts.